2006
DOI: 10.4319/lo.2006.51.1.0177
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope signatures of benthic invertebrates in arctic lakes indicate limited coupling to pelagic production

Abstract: We tested the hypotheses that benthic macroinvertebrates, especially chironomid larvae in the Tribe Chironomini, from small oligotrophic arctic lakes are only weakly linked to pelagic food sources, and that they are trophically linked to biogenic methane. All offshore benthic macroinvertebrates sampled from 20 lakes were depleted in 13 C compared with nearshore benthic macroinvertebrates. Nearshore macroinvertebrates had ␦ 13 C consistent with feeding on periphyton and/or terrestrial detritus. However, ␦ 13 C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
51
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 39 publications
8
51
0
Order By: Relevance
“…A sample of Chironomus anthracinus-type head capsules with a d 13 C value of -36.9% was found in sediments from a Siberian tundra pond. This is comparable to d 13 C values reported in living Chironomus larvae from Arctic lakes in Alaska, Sweden and Finland (Hershey et al 2006;Jones et al 2008). Chironomus species are the taxa most commonly reported to incorporate methane-derived carbon by feeding on MOB (Grey et al 2004;Jones et al 2008).…”
Section: Culturing Experimentssupporting
confidence: 68%
“…A sample of Chironomus anthracinus-type head capsules with a d 13 C value of -36.9% was found in sediments from a Siberian tundra pond. This is comparable to d 13 C values reported in living Chironomus larvae from Arctic lakes in Alaska, Sweden and Finland (Hershey et al 2006;Jones et al 2008). Chironomus species are the taxa most commonly reported to incorporate methane-derived carbon by feeding on MOB (Grey et al 2004;Jones et al 2008).…”
Section: Culturing Experimentssupporting
confidence: 68%
“…Almost one-third of the lakes contained chironomid larvae with an estimated 40% or more of their carbon biomass derived from methane, and as much as 70% in some circumstances. Jones et al (2008) C of chironomids and oligochaetes and dissolved oxygen concentration was also reported by Hershey et al (2006) from small arctic lakes in Alaska. Thus, it appears that the low d…”
mentioning
confidence: 97%
“…Kiyashko, Narita & Wada, 2001;Grey et al, 2004a;Deines & Grey, 2006;Hershey et al, 2006); this presumably relates to differences in redox conditions and hence in the availability of suitable microhabitats for MOB. However, even in offshore zoobenthos communities, it appears that chironomid larvae often exhibit low d…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Using multiple approaches (litter exclusion, gut contents, biomarkers, and stable isotopes), a number of authors have reported that some fishes and benthic invertebrates in streams and the littoral zones of rivers and lakes are indeed supported in part by terrestrial organic matter (e.g., refs. [9][10][11][12][13][14][15][16]. Demonstrating a terrestrial influence on pelagic food webs in lakes had been both more difficult and more controversial.…”
mentioning
confidence: 99%